Fear and employment during the COVID pandemic: Evidence from search behaviour in the EU - Wouter Van Der Wielen; Salvador Barrios Cobos (European Commission, Joint Research Centre (JRC), 2020)
The COVID-19 pandemic has inflicted an economic hardship unprecedented for the modern age. In this paper, we show that the health crisis and ensuing Great Lockdown, came with an unseen level of economic uncertainty. First, using a European dataset on country-level and regional internet searches, we document a substantial increase in people's economic anxiety in the months following the coronavirus outbreak. Moreover, we observe a significant, coinciding slowdown in labour markets and (durable) consumption. Second, our analysis shows that the ensuing fear was signific antly more outspoken in those EU countries hit hardest in economic terms. Finally, we show that economic anxiety during the Great Lockdown is similar or higher than during the Great Recession of 2007- 2009. Unprecedented policy actions, such as the short-term working schemes implemented or reformed at the onset of the COVID crisis, however, do not seem to have mitigated overall ec onomic anxiety.
Keywords: D12; D83; D84; E32; J60; 330; COVID-19; economic uncertainty; employment; expectations; Google Trends